2020
DOI: 10.35848/1347-4065/ab7fe3
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin probe force microscopic investigation of graphene-based derivatives

Abstract: We report the contact potential difference and work function variation among graphene-based derivatives, such as graphene oxide, reduced graphene oxide and pristine graphene, analyzed by Kelvin probe force microscopy in ambient conditions. The work function is strongly dependent on the amount of oxygen-containing functional groups, moisture or other adsorbates present on the material, and also on the environmental factors. With the removal of oxygen-containing functional groups, during reduction of graphene ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These results reveal that the systematic change in the CPD value and the corresponding work function depends on the composition and structure of the carbon carrier and the type of doped atoms. The measurement result of the GO work function is approximately 4.85 eV, and the work function of rGO was 4.70 eV, which is consistent with the trend reported previously. , Compared with GO, the decrease in the rGO work function and the increase in CPD may be due to the removal of oxygen functional groups and the improvement of electron conductivity on the rGO sheet. , However, the work function values of graphene-based catalysts are shown in the following order: GO (4.85 eV) > GO-N (4.35 eV) > GO-Fe–N (4.07 eV) and rGO (4.70 eV) > rGO-N (4.46 eV) > rGO-Fe–N (4.19 eV). The results indicate that the doping of heteroatoms (such as N and Fe atoms) will reduce the work function of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…These results reveal that the systematic change in the CPD value and the corresponding work function depends on the composition and structure of the carbon carrier and the type of doped atoms. The measurement result of the GO work function is approximately 4.85 eV, and the work function of rGO was 4.70 eV, which is consistent with the trend reported previously. , Compared with GO, the decrease in the rGO work function and the increase in CPD may be due to the removal of oxygen functional groups and the improvement of electron conductivity on the rGO sheet. , However, the work function values of graphene-based catalysts are shown in the following order: GO (4.85 eV) > GO-N (4.35 eV) > GO-Fe–N (4.07 eV) and rGO (4.70 eV) > rGO-N (4.46 eV) > rGO-Fe–N (4.19 eV). The results indicate that the doping of heteroatoms (such as N and Fe atoms) will reduce the work function of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…With the discovery and the development of graphene, graphene oxide (GO) and its reduced counterpart (reduced GORGO) has been regarded as the most promising precursors for pristine graphene because they can be scaled up to industrial requirement with controllable properties. , However, the lattice structure of GO is more complex than graphene obtained via mechanical exfoliation or chemical vapor deposition (CVD) due to the abundant defects, including oxygen-containing groups and lattice vacancies. This results in different chemical and physical properties in GO and RGO. On the other hand, RGO has properties that lie between GO and graphene. As a result, the interpretation of Raman spectra of GO and RGO is more complicated than that of other carbon nanomaterials .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to ME, epitaxial, and CVD-graphene, GO and RGO have many kinds of defects that could drastically change the surface potential, particularly due to the difference in charge transfer effect associated with the oxygen-containing functional groups [83,85,86]. By carrying out a systematic study on the dependence of WF on the oxygen content of GO during chemical reduction, Mishra et al have reported that the CPD value decreases (WF increases) with the removal of oxygen functionalities from GO (reduction of GO) [78].…”
Section: Surface Potential Of Graphene Oxide (Go) and Reduced Graphen...mentioning
confidence: 99%